INNOVATION AND USER BEHAVIOR FOR ENHANCEMENT IN BIKE SHARING PROGRAMME - Henry, Yu Chung; Paul, Lo Chi (MATTER: International Journal of Science and Technology, 2018)
Bike sharing is one of the fastest growing transportation mode for its environmental and economical benefits. Originated in Europe, more bike sharing programmes start up annually in major cities in the world. Hong Kong has its first bike sharing system in 2017. This paper first identifies usages and operational problems of bike sharing within the existing systems and examines how innovation in user behavior can enhance and improve the relationship between bike sharing entrepreneurs and citizen’s interest in sports facilities. By looking deeply into how innovation in bike sharing can change the mobility in the city, improving traffic network and connectivity in the urban setting, this study will identify key issues related to user behavior and other mis-use which lead to failure of most bike sharing operations. In essence, business operations, traffic departments and citizens can benefit from the insight of this study. By utilizing research methods such as case studies and questionnaire survey, the research compares and contrasts operational issues between Asian cities such as Hong Kong, Taiwan and Singapore. In addition, questionnaire survey will identify major bike usage pattern in daily commute use and therefore can shed light to the impact of bicycle mis-use and rationale. By identifying transportation pattern in high-density cities with relationship with urban amenities such as parking facilities, the research findings gained from this paper can be beneficial to other small and big business operators as well as city planners on how innovation can help or develop better bike-sharing systems.